2020
DOI: 10.1002/mrm.28423
|View full text |Cite
|
Sign up to set email alerts
|

B0 shimming of the human heart at 7T

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
14
0
2
Order By: Relevance
“…In practice, the aorta has a small cross-section area compared to the myocardium and, thus, for the 1D flow encoding, the B0 heterogeneity can be well managed with appropriate B0-shimming. However, data from our group showed that triggered B 0 mapping offers superior results and thus would be desirable for future studies [50].…”
Section: Plos Onementioning
confidence: 92%
“…In practice, the aorta has a small cross-section area compared to the myocardium and, thus, for the 1D flow encoding, the B0 heterogeneity can be well managed with appropriate B0-shimming. However, data from our group showed that triggered B 0 mapping offers superior results and thus would be desirable for future studies [50].…”
Section: Plos Onementioning
confidence: 92%
“…Another challenge of FW imaging that is even observed at 1.5T or 3T is given by ΔB 0 variations across the target region. At UHFs, however, ΔB 0 , as well as its spatial and temporal variations are larger compared with lower field strengths 46,47 . In addition, potential fluctuations in ΔB 0 as a function of the respiratory phase have been demonstrated at UHFs for the human heart, 48 showing local ΔB 0 changes of up to 100 Hz between exhale and deep inhale.…”
Section: Introductionmentioning
confidence: 93%
“…At UHFs, however, ΔB 0 , as well as its spatial and temporal variations are larger compared with lower field strengths. 46,47 In addition, potential fluctuations in ΔB 0 as a function of the respiratory phase have been demonstrated at UHFs for the human heart, 48 showing local ΔB 0 changes of up to 100 Hz between exhale and deep inhale. These respiration-induced ΔB 0 changes may have an impact on free-breathing 3D FW imaging at UHFs, especially when different respiratory phases are combined.…”
Section: Introductionmentioning
confidence: 93%
“…The second case study showed how sensitivity analysis helps deep learning-based software users to evaluate a newly trained model. More precisely, a model was demanded for segmentation of the heart in transversal ultra-high field MR images to improve B 0 shimming performance [36]. A model pre-trained on short-axis cine images at 7 T [32] was fine-tuned with very little additional data (90 images from 4 subjects).…”
Section: Case Study Ii: Model Robustnessmentioning
confidence: 99%